Outcome of haemopoietic stem cell transplantation in 21 patients with alpha-mannosidosis - Šáhó, Robert; Formánková, Renata; Eisengart, Julie B.; Lund, Allan Meldgaard; Videbaek, Cecilie; Gürbüz, Berrak Bilginer; Özbek, Namık Yaşar; Al Jasmi, Fatma; Ješina, Pavel; Feillet, François; Pochon, Cécile; Guémann, Anne-Sophie; et al. (Journal of inherited metabolic disease, 2025)
The outcomes of alpha-mannosidosis after hematopoietic stem cell transplantation (HSCT) are incompletely described. This retrospective multi-center study evaluated the outcomes of patients who underwent HSCT for their alpha-mannosidosis after 2010. Twenty-one children (11 females) with enzymatically and/or genetically confirmed alpha-mannosidosis, diagnosed at a mean age of 14 months (0-60 months), were included. The median age at HSCT was 3.9 years (10 months to 13.3 years) with a median follow-up of 2.3 years (0.3-14.1 years). Seventy-four percent (14/19) of patients received an unrelated graft while the rest had a matched sibling donor. Primary engraftment was reached in 17 of 21 patients; four patients required a second HSCT with successful subsequent engraftment. Nine patients had severe post-HSCT infections, five patients developed acute graft-versus-host disease (GvHD) (> = grade II), and one patient had chronic GvHD. No patient died during follow-up. Seven out of ten patients received enzyme replacement therapy both pre- and post-HSCT. Among children with clinical symptoms, improvement was documented in hepatomegaly (40% of patients before HSCT, down to 10% after), recurrent infections (62%/30%), and hearing disorder (85%/65%). In 13 patients with developmental data, outcomes after HSCT suggested at least mild delays persisted post-HSCT in the majority (85%), with some trends of higher functioning with earlier treatment. Findings suggest HSCT has shown notable improvements in safety and is associated with clinical benefit in alpha-mannosidosis. Neurodevelopmental findings require longer-term study to account for phenotypic diversity.